Impact of heat on mental health emergency visits: a time series study from all public emergency centres, in Curitiba, Brazil - Feriato Corvetto, Julia; Federspiel, Andrea; Sewe, Maquins Odhiambo; Müller, Thomas; Bunker, Aditi; Sauerborn, Rainer (BMJ open, 2023)
Objectives Quantify the risk of mental health (MH)-related emergency department visits (EDVs) due to heat, in the city of Curitiba, Brazil. - Design Daily time series analysis, using quasi-Poisson combined with distributed lag non-linear model on EDV for MH disorders, from 2017 to 2021. - Setting All nine emergency centres from the public health system, in Curitiba. - Participants 101 452 EDVs for MH disorders and suicide attempts over 5 years, from patients residing inside the territory of Curitiba. - Main outcome measure Relative risk of EDV (RREDV) due to extreme mean temperature (24.5°C, 99th percentile) relative to the median (18.02°C), controlling for long-term trends, air pollution and humidity, and measuring effects delayed up to 10 days. - Results Extreme heat was associated with higher single-lag EDV risk of RREDV 1.03(95% CI 1.01 to 1.05—single-lag 2), and cumulatively of RREDV 1.15 (95% CI 1.05 to 1.26—lag-cumulative 0-6). Strong risk was observed for patients with suicide attempts (RREDV 1.85, 95% CI 1.08 to 3.16) and neurotic disorders (RREDV 1.18, 95% CI 1.06 to 1.31). As to demographic subgroups, females (RREDV 1.20, 95% CI 1.08 to 1.34) and patients aged 18-64 (RREDV 1.18, 95% CI 1.07 to 1.30) were significantly endangered. Extreme heat resulted in lower risks of EDV for patients with organic disorders (RREDV 0.60, 95% CI 0.40 to 0.89), personality disorders (RREDV 0.48, 95% CI 0.26 to 0.91) and MH in general in the elderly ≥65 (RREDV 0.77, 95% CI 0.60 to 0.98). We found no significant RREDV among males and patients aged 0-17. - Conclusion The risk of MH-related EDV due to heat is elevated for the entire study population, but very differentiated by subgroups. This opens avenue for adaptation policies in healthcare: such as monitoring populations at risk and establishing an early warning systems to prevent exacerbation of MH episodes and to reduce suicide attempts. Further studies are welcome, why the reported risk differences occur and what, if any, role healthcare seeking barriers might play.
Gesehen am 08.04.2024